Lifestyle in flux: urbanization, dietary shifts, and endocrine health in emerging adulthood - Om Vijay Joshi; Ronit Rohidas Savale; Dinesh Nalage; Ashwini Biradar; Tejswini Sontakke (Reproductive Biology and Endocrinology)
Abstract Emerging evidence highlights the decline of testosterone levels among young males, linked to modern lifestyle shifts rather than aging alone. This exploratory cross-sectional study investigates the interplay between modifiable lifestyle factors and testosterone levels in 50 males aged 18–22 years, focusing on underrepresented variables such as exercise type, carbonated beverage intake, and sunlight exposure. Serum testosterone levels were measured via chemiluminescent immunoassay, and lifestyle data were collected through previously validated questionnaires. Multiple regression analyses revealed hypertrophy training (β = 20.3, p < 0.001), sunlight exposure > 60 min (β = 10.3, p = 0.03), and supplement use (β = 20.5, p < 0.001) as positive predictors of testosterone. Conversely, daily carbonated beverage consumption (β=−10.2, p = 0.01), tobacco use (β=−15.6, p < 0.001), and sleep deprivation (β=−18.2, p < 0.001) were significant negative correlates. Diet type influenced outcomes, with non-vegetarians showing higher testosterone (β = 8.7, p = 0.03) compared to vegetarians. Notably, BMI and chronic diseases were nonsignificant in this young cohort. These findings underscore the multifactorial nature of testosterone regulation, emphasizing holistic lifestyle interventions—such as resistance training, reduced ultra-processed food intake, and sleep optimization—as critical for endocrine health in urbanized youth. The study challenges traditional obesity-centric frameworks, advocating for holistic approaches to mitigate endocrine disruption in emerging adulthood.